Effect of imagery on free throw performance in young basketball players - Fortes, Leonardo de Sousa (2017)
The purpose of the present study was to analyze the effect of imaginary training on the free-throw performance in young basketball players. The sample consisted of 33 volunteers aged between 14 and 15 years, divided randomly into two groups: experimental (EG, n = 16) and control (CG, n = 17) group. Both groups underwent the same physical/technical training plan during eight weeks. The CG watched videos on the history of the Olympic Games, while the EG performed the imaginary training 3 times for week interspersed with the period of 48 hours. Performance in free-throw (hit percentage) was measured before and after 8 weeks. The results presented time (F(2, 31) = 19.65, p = .01) and group (F(2, 31) = 40.09, p = .001) effect. It was identified significant differences in free-throw performance between EG and CG after 8 weeks (F(2, 31) = 43.13, p = .01, d = .5). Thus, it was concluded that imaginary training was efficient to maximize free-throw performance in young basketball players.